2004
DOI: 10.1089/1540658041410641
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CHO Cells Stably Expressing a Gα16/zChimera for High Throughput Screening of GPCRs

Abstract: G protein-coupled receptors (GPCRs) are important therapeutic targets for drug discovery. The identification and characterization of new ligands ideally requires the use of high throughput assays that are applicable to all GPCR subtypes. To circumvent the problem of different GPCRs coupling to distinct intracellular second messenger pathways, we describe a new method that uses the chimeric Galpha protein 16z25 to facilitate this process. Stably expressed in Chinese hamster ovary cells, 16z25 allows G(i/o)- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…A number of G i -coupled receptors have recently been shown to be able to elevate intracellular Ca 2+ level by themselves. These include l-opioid [35], GABA B [27], muscarinic M 2 and M 4 [24], somatostatin SST 2 [36], and a 2 -adrenrgic [37] receptors. However, the underlying signaling mechanism utilized by these receptors is controversial.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of G i -coupled receptors have recently been shown to be able to elevate intracellular Ca 2+ level by themselves. These include l-opioid [35], GABA B [27], muscarinic M 2 and M 4 [24], somatostatin SST 2 [36], and a 2 -adrenrgic [37] receptors. However, the underlying signaling mechanism utilized by these receptors is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that functional FPRL-1 receptors are expressed in U87 human astrocytoma cells [15], and we have previously observed that several G i/o -coupled receptors including FPRL-1 can promote Ca 2+ mobilization upon overexpression in CHO cells [24]. We thus examined the ability of FPRL-1 to trigger increase in intracellular Ca 2+ as well as its downstream signaling pathway in U87 cells.…”
Section: Fprl-1 Receptors Mediate the Mobilization Of Intracellular Cmentioning
confidence: 98%
See 2 more Smart Citations
“…The same strategy worked equally well for G s -coupled receptors [27] . Chimeric G ␣ 16 subunits with broadened receptor-coupling capability have been successfully employed in high throughput screening platforms [23,[28][29][30] . Further efforts have been made to decipher the minimal requirements for switching the receptor-coupling specificity.…”
Section: Promiscuous Receptor Coupling Of G 16mentioning
confidence: 99%